Improving Process Design for Reaching Energy Efficiency, Environmentally Friendly, and Producing High Purity Methyl Chloride of Dehydrochlorination Process of Methanol and Hydrogen Chloride - Ramadhani, Muhammad Nuzul; Darmawan, Faisal Adhi; Mauludiyah, Fatimah; Nugraha, Muhammad Rizal Aditya (UPT Laboratorium Terpadu, Universitas Diponegoro, 2024)
Methyl chloride, also known as chloromethane, plays a vital role in producing various industrial goods. The current demand for methyl chloride in Indonesia exceeds production levels, making the design of a methyl chloride plant essential. This research focuses on improving methyl chloride production economically and operationally by exploring plant design using simulations that emphasize energy efficiency and high purity. The objective of this research is to develop a process design for producing methyl chloride from methanol and hydrogen chloride, aiming for energy efficiency, an environmentally friendly factory, and high-purity methyl chloride products. The research employed an iterative simulation method to compare the basic and modified processes for methyl chloride production. The process involved constructing a simulation model using Aspen HYSYS, analyzing the simulation results using Aspen Energy Analyzer V12, and iteratively adjusting process parameters until achieving the desired performance or results. The research findings indicate that the methyl chloride modification process exhibits a lower energy requirement compared to the methyl chloride base process. Moreover, the modification process demonstrates minimal carbon emissions, establishing it as a sustainable and environmentally friendly design. Additionally, the methyl chloride produced in the modification process achieves a higher percentage of purity. In the initial process, the methyl chloride purity stood at 98.17%, while in the modified process, it saw an elevation to 99.35%. Considering these three aspects, the modification process is conclusively more efficient than the basic process system. Copyright © 2024 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).